PENGARUH VARIABEL PENERIMAAN DANA ZISWAF, BOPO, DAN LABA/RUGI NONOPERASIONAL TERHADAP NPF GROSS DENGAN FIRM SIZE SEBAGAI VARIABEL MODERASI PERIODE 2018.Q1–2023.Q3 - Khusnul Khotimah, Retno Wahyuning; Hestya Budianto, Eka Wahyu (Politeknik Negeri Lhokseumawe, 2024)
Abstract :This study aims to determine and examine the effect of receiving ZISWAF, BOPO, and non-operating profit / loss on gross NPF with firm size as a moderation variable for the period 2018.Q1 – 2023.Q3. The sample used in this study is companies in the financial sector listed on the Indonesia Stock Exchange (IDX) in 2018-2023. The sampling technique used was purposive sampling, with a total sample of 5 banks for 6 years. The data analysis techniques used are Panel Data Regression Analysis and Moderated Regression Analysis (MRA) with the Eviews 12 application. The results showed that ziswa funds, BOPO and non-operating profit / loss showed a significant influence on the value of the company. This means that if the value of ziswa funds generated is higher, the funds can be used to strengthen the capital of Islamic financial institutions so that the risk of bad loans will be reduced. High BOPO levels have an impact on Gross NPF levels. Large operational costs can reduce the company's profitability. Good non-operating profit can help reduce NPF Gross by improving the company's financial stability and repayment ability, while large non-operating losses can increase credit risk and contribute to an increase in NPF Gross if not managed properly. Firm size shows a significant positive influence on company value. This means that if the resulting capital structure is high, it will cause a decrease in the value of the company, and vice versa. Then, in the interaction of moderation variables, probability can moderate ziswa funds, BOPO, non-operating profit / loss on NPF against the value of financial sector companies in the 2018Q1-2023Q3 period. Keywords: Islamic Banking,ZISWAF Fund, BOPO,profit and loss, NPF Gross, Firm Size.